2012
DOI: 10.1007/s00213-012-2954-z
|View full text |Cite
|
Sign up to set email alerts
|

The drug effects questionnaire: psychometric support across three drug types

Abstract: Rationale The Drug Effects Questionnaire (DEQ) is widely used in studies of acute subjective response (SR) to a variety of substances, but the format of the DEQ varies widely across studies, and details of its psychometric properties are lacking. Thus, the field would benefit from demonstrating the reliability and validity of the DEQ for use across multiple substances. Objective The current study evaluated the psychometric properties of several variations of DEQ items, which assessed the extent to which part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(146 citation statements)
references
References 33 publications
2
143
1
Order By: Relevance
“…Additive genetic models were also used as indicated in the Results section, with copies of the minor allele coded as 0, 1, and 2 for GG, AG, and AA genotype groups, respectively. Based on prior work indicating that the responses to nine DEQ items were correlated, we clustered nine responses into three domains representing aversive, pleasurable, and stimulatory effects (Morean et al, 2013). The average response for 'feel anxious', 'feel down', and 'feel bad' formed the aversive domain; the average response for 'like', 'feel good', and 'want more' formed the pleasurable domain; and the average response for 'feel stimulated', 'feel effects', and 'feel high' formed the stimulatory domain.…”
Section: Resultsmentioning
confidence: 99%
“…Additive genetic models were also used as indicated in the Results section, with copies of the minor allele coded as 0, 1, and 2 for GG, AG, and AA genotype groups, respectively. Based on prior work indicating that the responses to nine DEQ items were correlated, we clustered nine responses into three domains representing aversive, pleasurable, and stimulatory effects (Morean et al, 2013). The average response for 'feel anxious', 'feel down', and 'feel bad' formed the aversive domain; the average response for 'like', 'feel good', and 'want more' formed the pleasurable domain; and the average response for 'feel stimulated', 'feel effects', and 'feel high' formed the stimulatory domain.…”
Section: Resultsmentioning
confidence: 99%
“…Measures of subjective responses to MA (ie, the drug effects questionnaire; DEQ), MA craving (ie, MAUQ), and cardiovascular function (ie, heart rate and blood pressure) were collected prior to MA administration (ie, baseline) and then again at 5,10,15,20,30,60,90, and 120 min following the second 15-mg MA administration. The DEQ is an 11-item questionnaire that captures subjective effects (Morean et al, 2013) comprised of questions such as, 'How much do you feel any drug effects? ', 'How bad are the drug effects you are feeling right now?'…”
Section: Ma Administration Procedures and Measuresmentioning
confidence: 99%
“…PET studies using 11 C-raclopride have, more specifically, implicated ventral striatum (VS) dAMPH-induced DA release with self-reported dAMPH-induced euphoria (Drevets et al, 2001) or drug wanting (Leyton et al, 2002). Furthermore, an analysis using an earlier sample of the participants included in this study found a positive relationship between DA release in striatum measured with 18 F-fallypride PET and "Want More" drug ratings on the Drug Effects Questionnaire, DEQ (de Wit et al, 1986;Morean et al, 2013), after oral dAMPH (Buckholtz et al, 2010). Whether differences in dopaminergic functioning in other nodes of the mesocorticolimbic DA system impact subjective responses to dAMPH is currently unknown.…”
Section: Introductionmentioning
confidence: 73%
“…The Drug Effects Questionnaire (DEQ) has good psychometric properties (Morean et al, 2013) and is sensitive to the effect of dAMPH (Brauer et al, 1996;de Wit et al, 1986). DEQ values were recorded as proportions of the 100 mm scale (values range from 0 to 1).…”
Section: Drug Effects Questionnairementioning
confidence: 99%